Polar cap hot patches: Enhanced density structures different from the classical patches in the ionosphere. Issue 16 (26th August 2017) - Zhang, Q.‐H.; Ma, Y.‐Z.; Jayachandran, P. T.; Moen, J.; Lockwood, M.; Zhang, Y.‐L.; Foster, J. C.; Zhang, S.‐R.; Wang, Y.; Themens, D. R.; Zhang, B.‐C.; Xing, Z. Y.
Abstract: Based on in situ and ground‐based observations, a new type of "polar cap hot patch" has been identified that is different from the classical polar cap enhanced density structure (cold patches). Comparing with the classical polar cap patches, which are transported from the dayside sunlit region with dense and cold plasma, the polar cap hot patches are associated with particle precipitations (therefore field‐aligned currents), ion upflows, and flow shears. The hot patches may have the same order of density enhancement as classical patches in the topside ionosphere, suggesting that the hot patches may be produced by transported photoionization plasma into flow channels. Within the flow channels, the hot patches have low‐energy particle precipitation and/or ion upflows associated with field‐aligned currents and flow shears. Corresponding Global Navigation Satellite System (GNSS) signal scintillation measurements indicate that hot patches may produce slightly stronger radio signal scintillation in the polar cap region than classical patches. A new type of polar cap patches, "polar cap hot patches, " is identified to differentiate enhanced density structures from classical patches. Hot patches are associated with particle precipitations, ion upflows, field‐aligned currents, and shear flows in the polar cap. Hot patches may lead to slightly stronger ionospheric scintillations of GNSS signals in the polar cap region than classical patches. Key Points: A new type of polar cap patches, "polar cap hot patches, " is identified to differentiate enhanced density structures from classical patches Hot patches are associated with particle precipitations, ion upflows, field‐aligned currents, and shear flows in the polar cap Hot patches may lead to slightly stronger ionospheric scintillations of GNSS signals in the polar cap region than classical patches